Development Of Nursing Research In Saudi Arabia A Review Study (The Review of Diabetic Studies, 2024)
Introduction: The introduction explains how Nursing Research in Saudi Arabia has changed over time from being a marginal area of study in the academic fields to becoming one of the essential foundations of the National Health Care Strategy for Saudi Arabia. Nursing has changed position since the launch of the Health Sector Transformation Programme and Saudi Vision 2030 from that of a vocational, task oriented professional to that of an Evidence-based, independent Scientific Professional.Objective: The purpose of this systematic review is to create a detailed overview of the past and present state of Nursing Research in the Kingdom of Saudi Arabia through an analysis of old and existing literature.Method: This study's method follows the PRISMA 2020 guidelines for systematic reviews. A full systematic review search was performed in five electronic databases: PubMed, CINAHL, Scopus, Web of Science and The Saudi Digital Library. Only peer-reviewed articles published in English relevant to the Nursing profession in Saudi Arabia were included in this study. Screening and extraction of data from these studies was done using Covidence by two independent reviewers, and methodological quality was assessed using the Joanna Briggs Institute (JBI) standardised checklist. The analysis of the information included in these studies was conducted using Thematic Synthesis.Conclusion: Research being conducted in the field of nursing in the Kingdom has grown to be more developed, with more authorship from local Saudi scholars and an increased focus on digital health and more specialized clinical inquiries. While there is an increase in support by institutions for Evidence-Based Practice (EBP), especially for hospitals that are seeking Magnet Recognition, there are still many significant obstacles such as clinical workload, lack of protected research time, and little statistical literacy. There is a need for future efforts to have sustainable funding, to support mentorship opportunities between the academic setting and the clinical setting, and to leverage the Kingdom's current digital infrastructure to conduct some of the best interventional studies.